Dialog mit Hindernissen: Philosophie und Mathematik - Peckhaus, Volker (Von der Antike bis zur Gegenwart. Erlanger Streifzüge durch die Geschichte der Philosophie)

Active Common-Mode Voltage Cancellation for Three-Phase PWM Rectifier/Inverter Systems based on a New Topology - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert (Proc. 16th IEEE Applied Power Electronics Conf. (APEC))

High Dynamic Control of a Three-Level Voltage Source Converter Drive with Synchronous Motor and Active Front End - Böcker, Joachim; Janning, Jörg; Jebenstreit, Helmut (EPE’01, Graz)

Generalization of orthogonality principle to model solenoidal wound multiwinding transformers - Wallmeier, P. (Conference Record of the 2001 IEEE Industry Applications Conference. 36th IAS Annual Meeting (Cat. No.01CH37248))

Linear Drive System for the NBP Railway Carriage - Henke, M,; Yang, B.; Grotstollen, H.

CAE-tool for optimizing development of switched mode power supplies - Fröhleke, N.; Hahm, D.; Mundinger, H.; Njiende, H.; Wallmeier, P.; Puder, H. (APEC 2001. Sixteenth Annual IEEE Applied Power Electronics Conference and Exposition (Cat. No.01CH37181))

Improved setpoint adjustment for ultrasonic motors - Schulte, T.; Fröhleke, N. (2001 IEEE/ASME International Conference on Advanced Intelligent Mechatronics. Proceedings (Cat. No.01TH8556))

Pitch analysis and control design for the linear motor of a railway carriage - Yang, Bo; Henke, M.; Grotstollen, H. (IEEE Industrial Application Society International Conference (IAS01), Chicago, Illinois, USA)

Enhanced Analysis and Design Issues of a 3 Level DC/DC Converter with Zero Voltage Zero Current Switching - Fröhleke, N.; Schniedermann, M. (9th European Conference on Power Electronis and Applications (EPE01), Graz, Austria)

Development of Power Converter for High Power Piezoelectric Motors - Schulte, T.; Fröhleke, N. (MAGELEC 2001 2nd symposium on electroactive materials and their applications in electrical engineering,Toulouse, France)

Optimization of Inductors in Power Converters Feeding High Power Piezoelectric Motors - Njiende, H.D; Fröhleke, N. (Australian University Power Engineering Conf. (AUPEC'01), Perth, Australia)

Umfangslogik/Inhaltslogik - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 11: U–V)

Universalsprache - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 11: U–V)

Use/Mention - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 11: U–V)

Giuseppe Peano, Geometric Calculus According to the Ausdehnungslehre of H. Grassmann. Translated by Lloyd C. Kannenberg. Boston/Basel/Berlin: Birkhäuser 2000 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)

Hilbert’s Paradox - Peckhaus, Volker; Kahle, Reinhard (Reports Institut Mittag-Leffler)

Automatisierte Optimierung von induktiven Bauelementen für Stromrichteranwendungen - Wallmeier, Peter

Leibniz, Gottfried Wilhelm. "Die Grundlagen des logischen Kalküls: Lateinisch–deutsch, herausgegeben, übersetzt und mit einem Kommentar versehen von Franz Schupp", Meiner: Hamburg 2000 (Philosophische Bibliothek; 525) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wehmeier, Kai F., “Consistent Fragments of Grundgesetze and the Existence of Non-logical Objects”, In: Synthese 121 (1999), 309–328 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Kvasz, Ladislav, “Changes of Language in the Development of Mathematics”, In: Philosophia Mathematica (3) 8, Nr. 1 (2000), 47–83 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Schirn, Matthias (Hg.), "Frege: Importance and Legacy", Walter de Gruyter: Berlin 1996 (Perspectives in Analytical Philosophy; 13) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Heintz, Bettina. "Die Innenwelt der Mathematik. Zur Kultur und Praxis einer beweisenden Disziplin", Springer: Wien 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

van Atten, M.S.P.R., "Phenomenology of Choice Sequences", Zeno: Utrecht 1999 (Diss. Universität Utrecht 1999) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard. "Wissenschaftslehre §§ 579–718", hg. v. Jan Berg, Friedrich Frommann–Günther Holzboog: Stuttgart-Bad Cannstatt 2000 (Bernard Bolzano-Gesamtausgabe. Reihe I: Schriften. 14.3) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Janssen, Theo M.V., “Frege, Contextuality and Compositionality”, In: Journal of Logic, Language and Information 10, No. 1 (2001), 115–136 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hintze, Henning. "Nominalismus. Primat der ersten Substanz versus Ontologie der Prädikation", Alber Verlag: Freiburg/München 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Carnap, Rudolf. "Untersuchungen zur allgemeinen Axiomatik", hg. v. Thomas Bonk und Jesus Mosterin, Wiss. Buchgesellschaft: Darmstadt 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Pelletier, Francis Jeffry, “Did Frege Believe Frege’s Principle?”, Journal of Logic, Language, and Information 10 (2001), 87–114 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gefwert, Christoffer. "Wittgenstein on Mathematics, Minds and Mental Machines", Ashgate: Aldershot u.a. 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Casti, John L./DePauli, Werner. "Gödel: A Life of Logic", Perseus Publishing: Cambridge, Mass. 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Beaney, Michael (Hg.), "The Frege Reader. Selected Philosophical Writings", Blackwell: Oxford 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bueno, Otávio, “What is Structural Empiricism? Scientific Change in an Empiricist Setting”, In: Erkenntnis 50 (1999), 59–85 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Grosholz, Emily/Yakira, Elhanan. "Leibniz’s Science of the Rational", Franz Steiner: Stuttgart 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Spade, Paul Vincent (Hg.), "The Cambridge Companion to Ockham", Cambridge University Press: Cambridge 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Phraseologische Substitution und ihre Funktionen im Text - Ptashnyk, Stefaniya (Wirkendes Wort. Deutsche Sprache und Literatur in Forschung und Lehre. Heft 3/2001)

Фразеологiчні модифiкацiї: термінологічні проблеми [Phraseologische Modifikationen: Terminologische Probleme – ukr.] - Ptashnyk, Stefaniya (Вісник Львівського університету. Випуск 9: Серія іноземні мови)

Gabriel, Gottfried/Kienzler, Wolfgang (eds.), "Frege in Jena. Beiträge zur Spurensicherung. Tagungsbericht, Jena, Deutschland, 6.–7. Dezember 1996", Königshausen & Neumann: Würzburg 1997 - Peckhaus, Volker (Mathematical Reviews [Reprint von Zbl. 897.01002])

van Dalen, Dirk, “The Role of Language in Brouwer’s Work”, in: Ewa Orłowska (Hg.), Logic at Work. Essays Dedicated to the Memory of Helena Rasiowa, Physica-Verlag: Heidelberg 1999, 3–14 - Peckhaus, Volker (Mathematical Reviews)

„Grammatik in Deutsch-Lehrwerken“. Germanisten - Tagung in Karpacz (5.- 7. Sep-tember 2000) - Ptashnyk, Stefaniya; Fraczek, Agnieszka (Convivium. Germanistisches Jahrbuch Polen 2001)

Diagrammatic self-energy approximations and the total particle number - Schindlmayr, Arno; García-González, Pablo; Godby, Rex William (Physical Review B)
There is increasing interest in many-body perturbation theory as a practical tool for the calculation of ground-state properties. As a consequence, unambiguous sum rules such as the conservation of particle number under the influence of the Coulomb interaction have acquired an importance that did not exist for calculations of excited-state properties. In this paper we obtain a rigorous, simple relation whose fulfilment guarantees particle-number conservation in a given diagrammatic self-energy approximation. Hedin’s G0W0 approximation does not satisfy this relation and hence violates the particle-number sum rule. Very precise calculations for the homogeneous electron gas and a model inhomogeneous electron system allow the extent of the nonconservation to be estimated.

Exchange-correlation kernels for excited states in solids - Tatarczyk, Krzysztof; Schindlmayr, Arno; Scheffler, Matthias (Physical Review B)
The performance of several common approximations for the exchange-correlation kernel within time-dependent density-functional theory is tested for elementary excitations in the homogeneous electron gas. Although the adiabatic local-density approximation gives a reasonably good account of the plasmon dispersion, systematic errors are pointed out and traced to the neglect of the wave-vector dependence. Kernels optimized for atoms are found to perform poorly in extended systems due to an incorrect behavior in the long-wavelength limit, leading to quantitative deviations that significantly exceed the experimental error bars for the plasmon dispersion in the alkali metals.

Self-consistency and vertex corrections beyond the GW approximation - Schindlmayr, Arno (Recent Research Developments in Physics)

[Rez. v.] Marcus Weidner: Landadel in Münster 1600–1780. Stadtverfassung, Standesbehauptung und Fürstenhof. 2 Teilbde. (Quellen und Forschungen zur Geschichte der Stadt Münster, NF., Bd. 18/1 u. 2.) Münster, Aschendorff 2000 - Süßmann, Johannes (Historische Zeitschrift)

Wissenschaft und Gesellschaft in antiken Kulturen - Lloyd, Geoffrey (Revolutionen des Wissens. Von der Steinzeit bis zur Moderne)

Wissen und die Arten seiner Weitergabe - Goody, Jack R. (Revolutionen des Wissens. Von der Steinzeit bis zur Moderne)

Revolutionen des Wissens – eine Einführung - Fried, Johannes; Süßmann, Johannes (Revolutionen des Wissens. Von der Steinzeit bis zur Moderne)

Revolutionen des Wissens. Von der Steinzeit bis zur Moderne
Keywords: Antikenrezeption; Griechenland; Ägypten; Vor- und Frühgeschichte; Babylon; Perser; Wissenschaftsgeschichte; Bewußtseinsphilosophie; Bloch; Ernst; Benjamin; Walter; Mündlichkeit; Schriftlichkeit

Jenseits von Bildung und Liberalismus. Die radikale jüdische Erneuerungsbewegung in der Weimarer Republik - Aschheim, Steven E. (Revolutionen des Wissens. Von der Steinzeit bis zur Moderne)

Two-Dimensional Test Data Compression for Scan-Based Deterministic BIST - Liang, Hua-Guo; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE International Test Conference (ITC'01))

Deterministic BIST Scheme Based on Reseeding of Folding Counters - Liang, Hua-Guo; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Computer Research and Development, (Jisuanji Yanjiu yu Fazhan))